Novel anti-obesity drugs and plasma lipids. (April 2014) - Nikolic, Dragana; Toth, Peter P; Ferlita, Alessandra; Bartolo, Vittoria Di; Montalto, Giuseppe; Banach, Maciej; Rizzo, Manfredi
Obesity is a health problem of global, epidemic proportions and a major risk factor for chronic diseases resulting in accelerated morbidity and mortality. Dyslipidemia with a predominance of small dense LDL, impaired functionality of HDL particles, and increased serum levels of remnant particles due to impaired clearance of triglyceride-rich lipoproteins significantly heightens cardiovascular events in obese subjects. Pharmacotherapy in combination with lifestyle modification is the primary approach to reduce obesity-related cardiovascular risk. Although there are several potential anti-obesity drugs, orlistat is the only agent that remains available in the market. Lorcaserin and Qsymia ®, approved by the US FDA last year, and contrave with potential approval in 2014, are new anti-obesity drugs with promising therapeutic effects. Although these drugs can be associated with adverse side-effects, these agents have favorable effects on lipid profiles. However, the need for safer anti-obesity agents is clear.